Influence of flower functionality and pollination system on the pollen size-pistil length relationship - Fernández, Verónica Andrea (2009)
Twenty-five biotically pollinated plants of the Chaco Serrano Forest (Córdoba, Argentina) were studied in order to analyze whether ‘flower functionality’ is related to the relationship between pollen size and pistil length. Because flower functionality may act on the respective mean values of pollen size and pistil length rather than on intraspecific variation in these traits, we expected (1) a high positive correlation between pollen size and pistil length in a set of sympatric species, independent of their degree of pollination specialization or generalization; and (2) no interspecific correlation between the coefficients of variation (CVs) of those traits. On the other hand, on the assumption that pollinators are influencing the variation in floral traits (e.g. in pistil length) we expected lower mean phenotypic variation of pollen size and pistil length in pollination-specialist plants than in pollination-generalist ones. A positive correlation between pollen size and pistil length was found for the set of species, but not between the CVs of these traits. This trend was maintained when pollination-specialist plants were analyzed separately, but no statistical significance was obtained for the correlation in pollination-generalist plants. Contrary to our expectations, pollination-specialist plants did not show less mean intraspecific variation in floral traits than pollination-generalist plants. Therefore, the relationship between pollen size and pistil length among species suggests that the pollination system may be of less importance as a selective force than flower functionality.